Peran Guru Pendidikan Agama Islam (PAI) dalam Mengimplementasikan Pembelajaran Sifat-Sifat Terpuji Pada Siswa - Aras, Dini Aulia; Rasyid, Muhammad Rusdi; Umrah, St (Tarbiyah STAIN Sorong, 2017)
The role of the teacher as one of the components in the school that regulates the profession that plays a role in the teaching and learning process. The key to the success of schools in achieving educational goals in schools is in the hands of the teacher, he has a role in the process of growth, knowledge, skills, intelligence and attitudes and outlook on student life. Praiseworthy is something good that a person has. Being praiseworthy is a sign of the perfection of one's faith in God, Akhlakul karimah replaces praiseworthy qualities, the virtues of the virtue of the virtues that connect a person with tawadu, obedience, qana'ah, trust, and patience. The real role of the teacher lies only in the delivery material and the teacher who can be applied in accordance with what is intended for students, with students who are expected to be able to support and do what has been exemplified by the teacher. From these statements, the formulation of the problem taken by the researcher is about the role of the teacher in implementing the learning of commendable traits in grade VIII students of SMPN 03 Kab. Sorong and inhibiting factors for teachers in implementing learning of commendable nature in class VIII students of SMPN 03 Kab. Sorong. This research uses descriptive qualitative methods, while the data collection techniques that researchers use are observation techniques, interview techniques, and documentation techniques. The data analysis technique is done by observation, presenting data and drawing conclusions. The role of PAI teacher in implementing the commendable learning in the allowance with various habituation to draw character and commendable traits to students such as Dzuhur prayer in congregation, reading the Qur'an before starting learning, praying and much more so that it can be praiseworthy that is sought after by students only applied in the school environment but at home and in the community.